THE COMPARISON OF STUDENTS’ WRITING ABILITY IN DESCRIPTIVE TEXT INSTRUCTION BETWEEN USING DRAW-LABEL-CAPTION (DLC) AND JIGSAW TECHNIQUE - Yayah Safitri (Premise: Journal of English Education and Applied Linguistics, 2012)
The objectives of this research are to know the difference result of using DLC and Jigsaw technique toward students’ writing ability in descriptive text istruction  and to know which one is more effective of students’ writing ability in descriptive text instruction between learning by using DLC and Jigsaw technique.This research uses quantitative research. This research uses  Pre-Test and Post-test design. The result shos that DLC Technique is more effective technique than Jigsaw technique to improve of students’ writing ability in descriptive text instruction. Calculation results provide evidence that the posttest students in experimental class are better than control class. This can be seen when the posttest score of students compared with pretest score. The result showed that there was significant differences between pretest and posttest score (posttest>pretest). The results are consistence with the result of research Khoirul Anam (2010).It implies that DLC is preferable technique for future study.